Bark Beetle Effects on Fire Regimes Depend on Underlying Fuel Modifications in Semiarid Systems. (23rd January 2023) - Ren, Jianning; Hanan, Erin J.; Hicke, Jeffrey A.; Kolden, Crystal A.; Abatzoglou, John T.; Tague, Christina (Naomi) L.; Bart, Ryan R.; Kennedy, Maureen C.; Liu, Mingliang; Adam, Jennifer C.
Abstract: Although natural disturbances such as wildfire, extreme weather events, and insect outbreaks play a key role in structuring ecosystems and watersheds worldwide, climate change has intensified many disturbance regimes, which can have compounding negative effects on ecosystem processes and services. Recent studies have highlighted the need to understand whether wildfire increases or decreases after large‐scale beetle outbreaks. However, observational studies have produced mixed results. To address this, we applied a coupled ecohydrologic‐fire regime‐beetle effects model (RHESSys‐WMFire‐Beetle) in a semiarid watershed in the western US. We found that in the red phase (0–5 years post‐outbreak), surface fire extent, burn probability, and surface and crown fire severity all decreased. In the gray phase (6–15 years post‐outbreak), both surface fire extent and surface and crown fire severity increased with increasing mortality. However, fire probability reached a plateau during high mortality levels (>50% in terms of carbon removed). In the old phase (one to several decades post‐outbreak), fire extent and severity still increased in all mortality levels. However, fire probability increased during low to medium mortality (≤50%) but decreased during high mortality levels (>50%). Wildfire responses also depended on the fire regime. In fuel‐limited locations, fire probability increased with increasing fuel loads, whereas in fuel‐abundant (flammability‐limited) systems, fire probability decreased due to decreases in fuel aridity from reduced plant water demand. This modeling framework can improve our understanding of the mechanisms driving wildfire responses and aid managers in predicting when and where fire hazards will increase. Plain Language Summary: Bark beetle outbreaks have impacted millions of hectares of forest in western North America. Beetle‐caused tree mortality can increase or decrease wildfire hazards by altering surface fuel loading and decreasing leaf moisture. Previous studies have observed increases in fire following beetle attacks. However, others have found no change or a decrease. Such discrepancies can result from several interacting factors, such as how much time has passed since an outbreak, the level of tree mortality, and pre‐outbreak fuel conditions. To examine how these factors influence surface and crown fire characteristics in a semiarid watershed, we used a model that simulates interactions among hydrology, vegetation, beetle effects, and fire. We found that in the first 5 years after attack, surface fire probability and extent decreased due to decreases in plant productivity and fuel loading. Surface and crown fire severity had similar responses as surface fire extent. Following that, fire responses were a function of two counteracting forces: increases in fuel loading from delayed needle‐ and snag‐fall and wetter fuels from reduced plant water demand. The dominant force depended on fuel conditions. In fuel‐limited locations, fire increased with more fuel loads, whereas in fuel‐abundant locations, fire normally decreased due to wetter fuels. This research provides a practical tool for managers to better predict when and where fire hazards will increase. Key Points: Five years after beetle outbreak, fire probability decreased due to reduced vegetation productivity and fuel loading Six to fifteen years after outbreak, fire probability increased due to more fuel loading from snag‐fall Fifteen years after outbreak, fire probability decreased due to lower fuel aridity when mortality level was higher than 50%